Relationship between Students' Historical Awareness and their Appreciation of Local Cultural Heritage - Santos, Lilibeth C. (Future Science / FSH-PH Publications, 2021)
The K-12 curriculum brought a significant change in Social Studies/ Araling Panlipunan curriculum at the Basic Education level, but much still must be done to introduce relevant topics in history and culture following local contexts. As such, local historians and educators pursued its relevance to studying local history, particularly with the Kasaysayang Lokal (KASALO) ng Pampanga, to embark to the mind of todays' learners the local history of their pace. With this, the study aimed to assess the local awareness of Junior High School students and its correlation to their appreciation of cultural heritage. The study utilized descriptive-correlational research designed that aims to determine the relationship of the variables. The respondents of the study consisted of 281Junior High School students chosen through a simple random sampling technique. The results revealed that the students exhibited a slight awareness of their local history. Moreover, they have generally agreed to school-based initiatives to nurture cultural heritage appreciation. The Pearson-r correlation analysis revealed that the student's knowledge of KASALO did not significantly correlate to their appreciation of Kapampangan's local cultural heritage. The implications underlined the need for teachers to introduce more novel ways to integrate topics in local history in the AP classroom and strengthen local studies centers to promote the study of local history for the future.